Muscarinic Long-Term Enhancement of Tonic and Phasic GABAA Inhibition in Rat CA1 Pyramidal Neurons - Domínguez, Soledad; Fernández de Sevilla, David; Buño, Washington (Frontiers in Cellular Neuroscience, 2016)
ABSTRACT Acetylcholine (ACh) regulates network operation in the hippocampus by controlling excitation and inhibition in rat CA1 pyramidal neurons (PCs), the latter through gamma-aminobutyric acid type-A receptors (GABAARs). Although, the enhancing effects of ACh on GABAARs have been reported (Dominguez et al., 2014; 2015), its role in regulating tonic GABAA inhibition has not been explored in depth. Therefore, we aimed at determining the effects of the activation of ACh receptors on responses mediated by synaptic and extrasynaptic GABAARs. Here, we show that under blockade of ionotropic glutamate receptors ACh, acting through muscarinic type 1 receptors, paired with postsynaptic depolarization induced a long-term enhancement of tonic GABAA currents (tGABAA) and puff-evoked GABAA currents (pGABAA). ACh combined with depolarization also potentiated IPSCs (i.e., phasic inhibition) in the same PCs, without signs of interactions of synaptic responses with pGABAA and tGABAA, suggesting the contribution of two different GABAA receptor pools. The long-term enhancement of GABAA currents and IPSCs reduced the excitability of PCs, possibly regulating plasticity and learning in behaving animals.